2013
DOI: 10.1177/1063426613476092
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Tier 2 Interventions Conducted Within Multitiered Models of Behavioral Prevention

Abstract: To support students’ academic, behavioral, and social needs, many schools have adopted multitiered models of prevention. Because Tier 3 interventions are costly in terms of time and resources, schools must find efficient and effective Tier 2 interventions prior to providing such intense supports. In this article, we review the literature base on Tier 2 interventions conducted within the context of multitiered prevention models evidencing a Tier 1 behavioral plan. Article selection and coding procedures are des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 46 publications
(108 reference statements)
3
101
0
Order By: Relevance
“…First, although we conducted two different electronic searches as well as ancestral searches of three different literature reviews (Bruhn et al, 2014;Carter et al, 2011;Hawken et al, 2014), we did not hand search individual journals. Thus, it is possible we inadvertently missed articles that could have been included in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although we conducted two different electronic searches as well as ancestral searches of three different literature reviews (Bruhn et al, 2014;Carter et al, 2011;Hawken et al, 2014), we did not hand search individual journals. Thus, it is possible we inadvertently missed articles that could have been included in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Because that review included intervention studies with goal-setting components, we retrieved electronically all 81 articles reviewed by Carter et al Finally, currently published reviews on Tier 2 interventions (Bruhn, Lane, & Hirsch, 2014) and CICO (Hawken, Bundock, Kladis, O'Keeffe, & Barrett, 2014) were examined for additional articles that were not found in the first three searches. Tier 2 reviews were selected over Tier 3 given (a) their overlap in content found in the electronic searches, and (b) goal setting has been recommended for use as a low-intensity, resource-efficient, Tier 2 intervention (Lane, Menzies, Bruhn, & Crnobori, 2011;McDaniel, Bruhn, & Mitchell, 2015).…”
Section: Methods Article Search and Selection Proceduresmentioning
confidence: 99%
“…CICO is also one of the most researched (Bruhn, Lane, and Hirsch 2014) and utilised (Rodriguez, Loman, and Borgmeier 2016) behavioural interventions implemented within SWPBIS. However, maintaining the positive effects gained as a result of CICO support is not known.…”
Section: Adhd Symptoms and Inclusion With Pbismentioning
confidence: 99%
“…Research has shown CICO to be effective in reducing problem behavior with elementary and middle school students (Bruhn, Lane, & Hirsch, 2014;Cheney et al, 2009;Fairbanks, Sugai, Guardino, & Lathrop, 2007;Filter et al, 2007;Hawken, 2006;Hawken, Bundock, Kladis, O'Keeffe, & Barrett, 2014;Hawken & Horner, 2003;Hawken, MacLeod, & Rawlings, 2007;March & Horner, 2002;McCurdy, Kunsch, & Reibstein, 2007;Miller, Dufrene, Sterling, Olmi, & Bachmayer, 2015;Todd, Kaufman, Meyer, & Horner, 2007). In a recent review of 28 studies evaluating CICO, the intervention was found to decrease observed problem behavior, improve academic engagement or work completion, improve the percentage of DPR points, and reduce Office Discipline Referrals (ODRs; Hawken et al, 2014).…”
Section: Introductionmentioning
confidence: 99%